Predictors of Nonunion and Infectious Complications in Patients With Posttraumatic Subtalar Arthrodesis. Issue 10 (October 2016) - Dingemans, Siem A.; Backes, Manouk; Goslings, J. Carel; de Jong, Vincent M.; Luitse, Jan S. K.; Schepers, Tim
Abstract : Objective: The objective of the present study was (1) to identify predictors of both nonunion and postoperative wound infections (POWI) and (2) to assess the union and complication rate following posttraumatic subtalar arthrodesis (STA). Design: Retrospective comparative cohort study. Setting: Level 1 trauma center. Patients: All consecutive adult patients with STA following traumatic injuries between 2000 and May 2015. Intervention: STA for posttraumatic deformities. Main Outcome Measurements: Union (described as a combination of radiographic signs of osseous bridging and a clinically fused joint) and POWI as classified by the Centers for Disease and Control. Results: A total number of 93 (96 feet) patients met the inclusion criteria. Union was achieved in 89% of patients. For primary, secondary in situ, and secondary correction arthrodesis, these percentages were 94%, 84, % and 90%, respectively (NS). The union rate significantly increased over time ( P = 0.02). In 17 patients (18%), a POWI occurred, of which 2 were classified as superficial and 15 as deep POWIs. The POWI rate did not differ between the groups. Alcohol, nicotine, and drug abuse were not significantly associated with the occurrence of POWIs. Patients with an open fracture or an infection following open reduction internal fixation had a greater risk of a POWI following STA ( P = 0.03 and P = 0.04, respectively). Conclusions: We could not identify predictors for nonunion. In 18% of the patients, an infectious complication following surgery occurred. Patients with an open fracture or an infection after primary surgical treatment (ie, open reduction internal fixation) have a higher chance of POWIs following STA. The union rate following posttraumatic STA is 89%. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.